THE EFFICIENCY AND THE EFFECTIVENESS OF MARKETING FUNCTION OBSERVED BY MARKETING AUDIT (Single Case Study in PT Millenium Pharmacon International Tbk Malang Branch) - Bimanda, Mufti; Widijoko, Grace (Jurnal Ilmiah Mahasiswa FEB, 2016)
Research on marketing audit is a descriptive qualitative research which aimed to comprehend the effectiveness and the efficiency of marketing function in PT Millenium Pharmacon International Tbk Malang branch and to figure out what factors that led to ineffectiveness and inefficiency. This research discusses marketing function which is done through qualitative descriptive research method. The data are collected form field study, interview, and observation. Data analysis involves three elements of management audit which are criteria, cause, and effect. The scope of audit being discussed in this research are six marketing audit components which are marketing environment, marketing strategy, marketing organization, marketing system, marketing productivity, and marketing function. Based on the result that is done through comprehensive analysis, it concludes that marketing function has been managed in efficient and effective way in accordance to the applicable policy and regulation; however, the marketing organization need to be fixed where MPI need to hold more trainings for their employee to improve their technical skill, theories, conceptual, and moral in order to reach maximum result.Keywords  : PT Millenium Pharmacon International Tbk Malang branch, marketing audit, marketing function, effectiveness, efficiency, criteria, cause, effect, recommendation